Chest X-ray Film in Acute Myocardial Infarction - Tattersfield, A. E. (1969)
A total of 185 chest x-ray films taken on 50 consecutive admissions to a coronary care unit were assessed independently for specific abnormalities by three observers. The commonest abnormality was upper lobe pulmonary venous congestion. When this was present by itself it did not appear to affect prognosis. Pulmonary oedema occurred in 12 of the patients, was associated with more pronounced pulmonary venous congestion (but not necessarily with cardiac enlargement), and usually cleared within five days. Generalized cardiac enlargement and septal lines were rarely seen. Clinically silent non-segmental shadows were found in six patients. No consistent change in radiological abnormality was found in the first three days after infarction, but thereafter a gradual improvement occurred, so that before discharge the x-ray picture was nearly normal. There was good correlation between the presence and extent of lung crepitations and the presence of pulmonary oedema on the chest x-ray film. It is suggested that the chest x-ray film is a useful additional index of the severity of heart failure in myocardial infarction.